Dystonia and Cocaine Withdrawal - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
An acute dystonic episode in a 15-year-old girl during cocaine withdrawal is reported from the Departments of Neurology and Psychiatry, Albert Einstein College of Medicine, Bronx, N.Y. After 16 hours of observation in the hospital without receiving any drugs, she developed generalized dystonia, torticollis, extensor posturing, and high-pitched vocalizations.